2009
DOI: 10.1592/phco.29.1.128
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluations of Clinical Pharmacy Services: 2001–2005

Abstract: The objectives of this review were to summarize and evaluate studies that measured the economic impact of clinical pharmacy services published between 2001 and 2005 (inclusive) and to provide guidance on methodologic considerations to individuals performing such research in the future. A systematic literature search using the MEDLINE and International Pharmaceutical Abstracts databases was conducted to identify published economic evaluations of clinical pharmacy services. Studies were screened and then randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 33 publications
2
121
2
2
Order By: Relevance
“…14 We found very small numbers of patients with abnormal TSH and T4 lab results who were hospitalized or had an ER visit. 23 These services were mostly hospital based, which may account for the higher ROI compared with the present study. However, 2 ambulatory care clinics, which reported rates of $1.02 and $2.89, were included in the analysis by Perez et al…”
Section: ■■ Discussionmentioning
confidence: 63%
“…14 We found very small numbers of patients with abnormal TSH and T4 lab results who were hospitalized or had an ER visit. 23 These services were mostly hospital based, which may account for the higher ROI compared with the present study. However, 2 ambulatory care clinics, which reported rates of $1.02 and $2.89, were included in the analysis by Perez et al…”
Section: ■■ Discussionmentioning
confidence: 63%
“…In other words, reductions in costs or other economic benefits worth US$4.81 were achieved for each US$1 spent on clinical pharmacy services. 2 In a systematic review of 36 studies, Kaboli and others 3 identified 5 interventions by clinical pharmacists that improved outcomes for hospital patients. In addition, in an observational study of almost 3 million patients in US hospitals, 7 clinical pharmacy services were associated with reductions in mortality rate.…”
Section: Value For Money and Hospital Pharmacistsmentioning
confidence: 99%
“…1 Currently, direct patient care by clinical pharmacists within multidisciplinary teams is recognized as one of the best pharmacy practice models because it minimizes risks, care costs, morbidity and mortality rates, as well as time spent in hospital; it also improves pharmacotherapy results. [2][3][4][5][6][7][8][9] Several initiatives and standards of practice for clinical pharmacy have been proposed around the world. These proposals promote the transformation of clinical pharmacy services through participation of pharmacists as providers of direct patient care, counselling, and support to medical and nursing staff in their decision-making.…”
Section: Introductionmentioning
confidence: 99%